STUDI POLA KONSUMSI TEH DI INDONESIA UNTUK MENDUKUNG DIVERSIFIKASI PRODUK YANG BERKELANJUTAN (A Study of Tea Consumption Pattern in Indonesia Toward Sustainable Product Diversification) - Hafiizh Prasetia; Arief Ameir Rahman Setiawan; Teuku Beuna Bardant; . Muryanto; Ahmad Randy; Muthia Syafika Haq; Adhi Irianto Mastur; Sugeng Harianto; Nova Annisa; Anny Sulaswatty (Biopropal Industri, 2020)
Research to explore consumer perspective toward tea product requirements has been being emphasized around the globe, as well as the advancing variety of consumer demand and market competitiveness. Particularly in Indonesia, broader market needs and government relevant policies toward environmental consideration made these issues also need to be significantly addressed. This study aimed to analyze tea in consumption patterns Indonesia to support diversified sustainable products. The research design was conducted using survey method. A questionnaire was developed using structured interviews, with the number of respondents as many as 188 people. This survey was accommodating general type of tea such as green tea, white tea, black tea, etc. The result showed that respondents’ preferences toward tea belong to tea bags the most, with percentage 57.45%, powdered tea 28.19% and ready to drink tea 14.36%. Respondents age of 31-40 years old most widely consumed tea everyday (1.90 cup.day-1). As many as 78.19% of respondents were chose to consumed plain tea, followed by milk added tea 12.23% and creamer added tea 9.57%.   Further analysis using the Likelihood Ratio Test showed that age, gender and occupation factors were not a significant factor in the variety of tea types. To support the sustainable tea industry consumer behavior is also very important to be studied because consumers usually ask for high production standards but with a cheap cost.Keywords: consumption pattern, preference, product diversification, sustainable industry, teaABSTRAKPenelitian mengenai eksplorasi perspektif konsumen terhadap persyaratan produk teh telah menjadi perhatian dunia, seiring dengan meningkatnya permintaan konsumen dan daya saing pasar. Khususnya di Indonesia, kebutuhan pasar yang lebih luas dan kebijakan pemerintah yang relevan terhadap pertimbangan lingkungan membuat masalah ini juga perlu ditangani secara signifikan. Penelitian ini memiliki tujuan untuk menganalisis pola konsumsi teh di Indonesia untuk mendukung diversifikasi produk yang berkelanjutan. Desain penelitian dilakukan dengan menggunakan metode survei. Kuesioner dikembangkan menggunakan wawancara terstruktur, dengan jumlah responden sebanyak 188 orang. Survei ini mengakomodasi teh secara umum, seperti teh hijau, teh putih, teh hitam, dan lain-lain . Hasil penelitian menunjukkan preferensi responden terhadap teh yang paling dominan adalah jenis teh celup (57,45%), teh serbuk (28,19%) dan teh siap minum (14,36%). Responden dengan usia 31-40 tahun paling banyak menkonsumsi teh setiap hari (1,90 gelas.hari-1). Sebanyak 78,19% responden memilih konsumsi teh tawar setiap hari, diikuti oleh teh dengan susu 12,23% dan teh dengan krimer 9,57%. Hasil analisis lebih lanjut menggunakan Likelihood Ratio Test, didapatkan bahwa antara variabel usia, jenis kelamin dan pekerjaan tidak terdapat pengaruh yang signifikan dalam pemilihan jenis teh.Kata kunci: diversifikasi produk, industri berkelanjutan, pola konsumsi, preferensi, teh